The Michael Porter Diamond approach. Level of international competitiveness of the Mennonite cheesemaking industry in Cuauhtémoc, Chihuahua, Mexico - Cavazos González, Laura Elizabeth (2022)
Faced with globalization and its impacts on the promotion of trade, local consumers gained access to international brands and entrepreneurs were able to offer their goods and services in other climes, translating into an economic benefit. Unfortunately, many artisanal businesses, such as the cheesemakers of Cuauhtémoc in the state of Chihuahua, Mexico, do not enjoy these same effects, as they fail to implement technical processes or marketing strategies and their commercial vulnerability increases as a result. This study employed Michael Porter’s diamond model to assess this industry in terms of its competitiveness. The research is mixed: 26 cheesemakers were sampled, three experts in the field were interviewed, and the data was analyzed using SPSS software. It is concluded that the cheese cluster presents weaknesses in the relationships with suppliers and in the marketing networks, while a notable strength is the high product quality. Given these findings, an intercultural negotiation strategy between the various actors is proposed in order to maximize the potential of this distinctive regional product.